STAY HEALTHY AND HAPPY IN THE OLD AGE THROUGH ELDERLY EXERCISES AT PERUMDA RT 02, CANDI MULYO, JOMBANG - Hidayah, Ardiyanti; Anggraini, Rista Dian; Farida, Siti Nur; Aminati, Fifi Ratna; Niah, Najah Soraya (Library Unit collaborates with the Institute for Research and Community Service, College of Health Sciences Husada Jombang, 2024)
Advances in science and technology as well as socio-economic improvements affect people's health and life expectancy, resulting in an increase in the number of elderly people. This increase in the number of elderly people affects various lives. This service activity aims to improve the quality of life, knowledge and abilities of the elderly in their old age. The activity was carried out on Sunday, January 14 2024 at Perumda RT 02 Candi Mulyo, Jombang. The targets for implementing this community service activity are the elderly who live in Perumda RT 02 Candi Mulyo, Jombang. There were 30 participants who took part in this activity. Activities run safely and smoothly. Participants looked enthusiastic in participating in the activity. After the activity takes place, the community service activity implementer carries out a final evaluation of the activity. The results of the final evaluation showed that all participants understood how to improve their quality of life, knowledge and ability to carry out physical activity training in the form of elderly exercise.